Prevalence and factors associated with multidrug resistant Escherichia coli carriage on chicken farms in west Nile region in Uganda: A cross-sectional survey. - Ceaser Adibaku Nyolimati; Jonathan Mayito; Emmanuel Obuya; Atim Stella Acaye; Emmanuel Isingoma; Daniel Kibombo; D M Byonanebye; Richard Walwema; David Musoke; Christopher Garimoi Orach; Francis Kakooza (PLOS Global Public Health)
Infections with multi-drug-resistant (MDR) pathogens in food-animals threaten public health and food security. However, the epidemiology and factors associated with MDR Escherichia coli (MDR E. coli) on Ugandan farms are not well known. This study investigated the prevalence, resistance patterns and factors associated with MDR E. coli carriage on chicken farms. Escherichia coli was isolated from each of the 158 chicken farms sampled. The disc diffusion method for susceptibility testing was performed. Clinical breakpoints were interpreted according to Clinical and Laboratory Standards Institute guidelines. MDR was defined as resistance to three or more classes of antibiotics. MDR E. coli prevalence on chicken farms was 62.7% (95% CI: 55.0-70.3). High resistance was observed against ampicillin 79.8% (95% CI: 72.7-85.4), tetracycline 72.8% (95% CI: 65.2-79.2), cotrimoxazole 55.7% (95% CI: 47.8-63.3), and ciprofloxacin 38% (95% CI: 30.7-45.9). Male farm managers (Adjusted prevalence ratio [APR] = 0.72, CI: 0.55-0.93), attainence of at least secondary education (APR = 0.64, CI: 0.46-0.88) and administration of recommended antibiotic doses (APR = 0.76, CI: 0.59-0.96) posed a lower risk of MDR E. coli carriage while farms without footbaths posed a heighten risk (APR = 1.48, CI: 1.16-1.88). MDR E. coli carriage was highly prevalent on chicken farms in Uganda. This study underscores the urgent need for antimicrobial stewardship and improved infection prevention strategies on chicken farms.